2019
DOI: 10.1039/c9nr00082h
|View full text |Cite
|
Sign up to set email alerts
|

Thulium doped LaF3 for nanothermometry operating over 1000 nm

Abstract: The use and applications of infrared emitting rare-earth luminescent nanoparticles as nanothermometers have attracted a great deal of attention during the last few years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…[31,35,37,[87][88][89][90][91] The shielded nature of the 4f orbitals and the resulting 4f n → 4f n -based narrow emission peaks at well-defined wavelengths allow to accurately measure LIRs without substantial spectral overlap. [87][88][89][90][91] If doped into thermally stable inorganic nano-or microcrystalline hosts, lanthanides thus found many promising applications such as Pr 3+ , [19,[92][93][94][95] Nd 3+ (often sensitized with Yb 3+ ) [33, or Tm 3+ [122][123][124] in the field of room temperature sensing and thermal bioimaging. Er 3+ and Yb 3+ is the traditional lanthanide couple for upconversion-based in vivo imaging, [125][126][127][128][129][130][131][132][133] or in situ temperature monitoring of catalytic reactions or flow reactions in microfluidic devices.…”
Section: Introductionmentioning
confidence: 99%
“…[31,35,37,[87][88][89][90][91] The shielded nature of the 4f orbitals and the resulting 4f n → 4f n -based narrow emission peaks at well-defined wavelengths allow to accurately measure LIRs without substantial spectral overlap. [87][88][89][90][91] If doped into thermally stable inorganic nano-or microcrystalline hosts, lanthanides thus found many promising applications such as Pr 3+ , [19,[92][93][94][95] Nd 3+ (often sensitized with Yb 3+ ) [33, or Tm 3+ [122][123][124] in the field of room temperature sensing and thermal bioimaging. Er 3+ and Yb 3+ is the traditional lanthanide couple for upconversion-based in vivo imaging, [125][126][127][128][129][130][131][132][133] or in situ temperature monitoring of catalytic reactions or flow reactions in microfluidic devices.…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] Recently, Ximendes et al reported a similar concept using LaF 3 nanoparticles doped with high concentrations of Tm 3+ , which showed cross-relaxation (i.e., partial energy transfer between two identical ions). [21] However, the working mechanism of energytransfer thermometers is complicated because it does not only depend on relaxation processes within an ion but also involves interactions between different ions. Consequently, it has not yet been possible to develop a quantitative method that predicts the accuracy and the precision of energy-transfer thermometers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some researchers have been involved in the study of nanometer temperature in nanoparticles under hyperthermia conditions. In most of the studies, this local temperature is accurately but indirectly determined by the use of an external element as luminescent optical labels (as Ag 2 S, PbS, and CdSe/CdS/ZnS quantum dots), upconversion emitters (Er 3+ , Yb 3+ , Nd 3+ , Eu 3+ , and/or Tm 3+ -doped nanomaterials ), thermosensitive polymers, , or thermal-denaturation of DNA, which are attached to the heat nanogenerators activated by means of an alternating magnetic field or NIR-light. Direct measurements have been also proposed based on the analysis of thermal gradients generated in plasmonic systems which are only suitable for those systems which display such specific physical properties .…”
mentioning
confidence: 99%